2014
DOI: 10.1017/pasa.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Observations of AB Doradus

Abstract: We have observed the bright, magnetically active multiple star AB Doradus in a multiwavelength campaign centring around two large facility allocations in November 2006 and January, 2007. Our observations have covered at least three large flares. These flares were observed to produce significant hardening of the X-ray spectra during their very initial stages. We monitored flare-related effects using the Suzaku X-ray satellite and the Australia Telescope Compact Array (ATCA) at 3.6 and 6 cm. Observations at 11 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The resulting fluxes were converted to luminosity using the distance of 14.85 pc. The quiescent fluxes in 0.3-10.0 keV using Suzaku data during the years 2006 and 2007 are taken from Slee et al (2014). The evolution of quiescent luminosity is summarized in Table B1 in Appendix B and is plotted in Figure 3.…”
Section: Long-term X-ray Activitymentioning
confidence: 99%
“…The resulting fluxes were converted to luminosity using the distance of 14.85 pc. The quiescent fluxes in 0.3-10.0 keV using Suzaku data during the years 2006 and 2007 are taken from Slee et al (2014). The evolution of quiescent luminosity is summarized in Table B1 in Appendix B and is plotted in Figure 3.…”
Section: Long-term X-ray Activitymentioning
confidence: 99%
“…Indian scientists have been playing a leading role in establishing solar and heliospheric science as one of the key science objectives of the MWA and continue to lead it (Oberoi & Kasper 2004;Oberoi & Benkevitch 2010;Bowman et al 2013;Beardsley et al 2020). Though the bulk of the work by the Indian community has been at frequencies overlapping with the SKAO-Low, the future plans involve making use of the SKAO-Mid frequencies as well.…”
Section: (): V-volmentioning
confidence: 99%
“…Multi-wavelength flare studies can be (and have been) used to derive information on flare physical parameters, the properties of the nonthermal electrons and the coronal magnetic field strengths, etc., which are unobtainable from X-ray data alone. For more information, see White et al (2011), who review the extensive studies of solar flares done using simultaneous radio and hard X-ray bands, and Slee et al (2014) for a recent example of such a multi-wavelength campaign which observed 3 flares from the nearby young star AB Dor.…”
Section: Impact Of Stellar Flares On Planetary Companionsmentioning
confidence: 99%